Effects of global postural re-education on stress and sleep quality in health sciences female students: a randomized controlled trial pilot study - Rodríguez-Aragón, Manuel; Varillas-Delgado, David; Gordo-Herrera, Javier; Fernández-Ezequiel, Alba; Moreno-Heredero, Berta; Valle, Noelia (Frontiers in Psychiatry, 2024)
Objective: The purpose of this study was to determine, for the first time, whether the application of a self-management program with global postural re-education (GPR) influences stress and sleep quality in female health science students. Methods: In this randomized controlled trial pilot study, forty-one female health science students were randomized into a control group (n=21) and an intervention group (n=20). Participants underwent 8 weeks of self-management with and without GPR, after familiarization and therapy training. Outcomes included the State-Trait Anxiety Inventory (STAI) questionnaire and cortisol levels in saliva measured with the "CORTISOL Saliva ELISA SA E-6000" kit. Sleep quality was measured with the Pittsburgh Sleep Quality Index (PSQI) and a Sleep Diary; total sleep time (TST), sleep onset latency (SOL), wakefulness after sleep onset (WASO), sleep efficiency (SE), and perceived sleep quality or satisfaction were assessed using the Likert scale. Results: After self-treatment with GPR, participants in the intervention group showed lower cortisol levels compared to the control group (p = 0.041). Additionally, the intervention group demonstrated statistically significant improvements in sleep quality according to their PSQI (p = 0.010), STAI (p = 0.043), SOL (p = 0.049), and SE (p = 0.002). Conclusion: This study shows that self-management through GPR helps reduce stress and improve sleep quality in female health science students.